Nanostructure Polyaniline (PANI) Decorated TiO2 Nanocomposite as Efficient Heterogeneous Catalyst - Handore, Kalpana N.; Sharma, Sumit; Jagtap, Smita; Chabukswar, Vasant V.; Sable, M.J.; Gujar, R.A.; Gawande, S.H. (Journal of Research Updates in Polymer Science, 2024)
The paper describes the synthesis of conducting polyaniline-TiO2 (PANI-TiO2) nanocomposite by chemical oxidative polymerization method using aniline as a monomer. TiO2 nanoparticles were synthesized by sol gel method using TiCl4 and ethanol. Ultrasound synthesized TiO2 nanoparticles and nanocomposite were characterized by various spectroscopic techniques UV, FT-IR, XRD, SEM and TGA. The XRD pattern confirms the appearance of sharp diffraction patterns indicating the small sized, high purity TiO2 nano particles are highly agglomerated with spherical morphology. The PANI-TiO2 nanocomposite was employed as a promising heterocyclic, reusable catalyst for most of the organic synthesis. The advantages of this methodology are mild reaction conditions with short reaction time, excellent yields, low loading and reusability of catalyst.